New Series of D-efficient Covariate Designs under BIBD set-up (International Journal of Statistical Sciences, 2024)
In the present study, an effort has been made to construct D-efficient covariate designs in BIB design (v, b, r, k and λ) set-up when either one of k and r is odd or both k and r are odd numbers and Hadamard matrix of order k i.e., Hk does not exist. For all the developed D-efficient designs, the covariates are mutually orthogonal to each other. The methods of construction of D-efficient covariate designs are developed with the help of a new matrix viz., Special Array (Das et. al., 2020). In this article, the series of developed D-efficient covariate designs are not available in the existing literature.International Journal of Statistical Sciences, Vol.24(1), March, 2024, pp 15-30